2021
DOI: 10.1108/ramj-09-2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Life dissatisfaction among students: exploring the role of intrapersonal conflict, insufficient efforts and academic stress

Abstract: Purpose The study focuses on academic stress among the students due to insufficient efforts and intrapersonal conflicts amid the COVID-19 situation. The purpose of this study is to measure the mediating role of academic stress between life dissatisfaction and adequate steps and intrapersonal conflicts. Design/methodology/approach The researcher had surveyed 729 students from the two states, including Haryana and Punjab and 716 responses were used for analysis. These respondents were approached in April–May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
(69 reference statements)
1
4
0
Order By: Relevance
“…Academic stressors are stress experienced by students due to problems related to the learning process or learning activities, such as test anxiety or stress management. Consistent with the opinion above (Anju et al, 2021), they found that academic stress is a condition or situation in which there is a mismatch between environmental demands and the considerable resources of students. As such, they are increasingly burdened with various restrictions and demands, and academic stress stems from the pressure to demonstrate performance and excellence in an increasingly competitive academic environment.…”
Section: Discussionsupporting
confidence: 76%
“…Academic stressors are stress experienced by students due to problems related to the learning process or learning activities, such as test anxiety or stress management. Consistent with the opinion above (Anju et al, 2021), they found that academic stress is a condition or situation in which there is a mismatch between environmental demands and the considerable resources of students. As such, they are increasingly burdened with various restrictions and demands, and academic stress stems from the pressure to demonstrate performance and excellence in an increasingly competitive academic environment.…”
Section: Discussionsupporting
confidence: 76%
“…In other words, weight-based teasing is one of the reasons behind increased depression-linked cases in Indian college students. Other factors can be cyberbullying (Bansal et al ., 2022), techno-ethical stress (Verma et al ., 2022), (Anju et al ., 2021) or even Brain Emotional Systems (Giacolini et al ., 2021). Hence, the present study further expanded upon Beck's (1967) Cognitive Theory on depression.…”
Section: Discussionmentioning
confidence: 99%
“…Life dissatisfaction has been correlated with unstable and negative emotions that affect people's wellbeings. People experience more life dissatisfaction when they have low quality of life pertaining to financial status, health, and freedom (Punia et al, 2021). Thus, it is not surprising that the economic pressure over more than 2 years during the pandemic has greatly impacted financial health as well as mental health of many.…”
Section: Discussionmentioning
confidence: 99%